Factors determining 800-m running performance in young male athletes - Cruz, R.; Bertuzzi, R. C.; Alves, D. L.; Azevedo, R.; Castro, P. H.; Freitas, J. V.; Lima-Silva, A. E.; de Oliveira, F. R.; Lima, J. R. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of the present study was to identify determinant variables on 800-m running performance in young male athletes derived from field tests and biological maturity. METHODS: A total of 89 athletes, aged between 13 and 15 years old, performed a 800-m running trial and a battery of tests which involved anthropometric measurements, a running anaerobic test (RAST), a flexibility test (sit-and-reach), a counter movement jump test and progressive test for aerobic fitness evaluation. A stepwise multiple regression model selected three independent variables to explain the variance in 800-m running performance trial: peak of aerobic speed (PAS), total time of all sprints (RAST) and predicted mature stature (PMS). RESULTS: The PAS speed explained 73.6% (P<0.01) of the variance, whereas the RAST and PMS accounted for additional 7.7% (P<0.01) and 0.9% (P<0.05), respectively. Taken together, these variables explained 82.2% of the overall 800-m running performance. CONCLUSIONS: The results indicate that the 800-m running performance might be explained mainly by aerobic (PAS) and anaerobic metabolisms (RAST). Beyond the traditional variables of performance in 800-m running trial, the biological maturity must be considered in regard of endurance performance of young athletes.